From time and space: science fiction and its present moment - Jones, Andrew, author; Eskew, Doug, advisor; Souder, Donna, committee member; Morales, Juan, committee member (Colorado State University. Libraries, 2012)
In this paper, I will argue that science fiction (sf) is typically misunderstood as a predictive text but is actually firmly and permanently grounded in the time it was created. Sf, as I present it, can be seen as more of what Mendlesohn calls "a product rather than a critic of social patterns" (120). An example of sf that is typically misunderstood as critic rather than product of its time is Star Trek, the 1960s television series. I show through Pierre Bourdieu's theories of language as symbolic power that despite Star Trek's hopeful view of an integrated future, thanks to its "USS Earth" metaphor, the show's content develops a Eurocentric market through its linguistic capital of rank and professional titles, or what Bourdieu calls "investiture" (119). Though the USS Enterprise promotes an environment and future where diversity and equality are commonplace, the ship's crew are never so unified that officers of lower rank, alien origin, or non-Euro-American descent are allowed to forgo the laws of classification. In fact, I argue that these laws are never ignored or suspended except between Captain Kirk and Dr. "Bones" McCoy, because they are able to negotiate their capital and manipulate their market in an exchange of "doctor/Captain" for the more familiar "Bones/Jim." Kirk and Bones prevail as embodiments of a Eurocentric patriarchy in a television series designed to bridge 1960s race and gender gaps. In studying Star Trek I will show how sf is a form that allows for a more accurate study of the past instead of the future. Ultimately, my critique of Star Trek shows how sf reflects its present moment in order to promote a new way of thinking about sf criticism.